Segmental abdominal wall paresis caused by lateral low thoracic disc herniation - Stetkarova, Ivana; Chrobok, Jiri; Ehler, Edvard; Kofler, Markus (Spine, 2007)
STUDY DESIGN: Clinical, radiologic, and neurophysiologic description of 2 cases. OBJECTIVE: To describe 2 cases with spontaneous deep unilateral abdominal pain as the first symptom of thoracic disc herniation at a low thoracic vertebral level, further manifested by unilateral partial paresis of the obliquus abdominis muscle. SUMMARY OF BACKGROUND DATA: Clinical manifestation of lateral thoracic disc herniation with electrophysiologic results and conservative therapy as treatment of choice when spinal cord functions are preserved. METHODS: Magnetic resonance imaging revealed bilateral paramedian disc protrusions at T12-L1 in Patient 1 and foraminal herniation at T10-T11 and paramedian herniation at T11-T12 in Patient 2. Electromyography (EMG) and evoked potentials were investigated in the acute stage and after 6 months. RESULTS: Spontaneous activity on needle EMG confirmed axonal root impairment. Somatosensory and motor-evoked potentials were within normal limits and excluded spinal cord involvement. Nonsteroidal anti-inflammatory drugs and periradicular injection of steroids and local anesthetics rendered both patients pain-free. Normalization of muscle strength within 3 to 6 months was accompanied by EMG findings of reinnervation. CONCLUSION: Lateral disc herniation causing compression of a thoracic root associated with unilateral segmental paresis of the abdominal wall is a rare condition. Despite EMG documentation of axonal root lesion, however, a purely conservative therapeutic approach may be considered treatment of choice in cases without spinal cord involvement.
Keywords: svalová síla; bolesti břicha; Steroids; evokované potenciály; Paresis; výsledek terapie; Evoked Potentials; Spinal Nerve Roots; obnova funkce; Middle Aged; břišní svaly; mužské pohlaví; Abdominal Muscles; Adult; antiflogistika nesteroidní; Intervertebral Disc Displacement; Thoracic Vertebrae; magnetická rezonanční tomografie; Muscle Strength; steroidy; Magnetic Resonance Imaging; Abdominal Pain; ženské pohlaví; Recovery of Function; Humans; elektromyografie; Anti-Inflammatory Agents, Non-Steroidal; paréza; Electromyography; lidé středního věku; míšní kořeny; výhřez meziobratlové ploténky; hrudní obratle; dospělí; Female; Treatment Outcome; lidé; Male